Currency crisis and stock price behaviour : Evidence from the Kuala Lumpur composite index / Anuar Hj. Wahhab…[et al.] - Hj. Wahhab, Anuar; Ab Rahman, Nik Muhd Naziman (Research Management Institude, 2002)
This research uses an error correction model to explore the asymmetric effects of five different exchange rates on the Kuala Lumpur Composite Index (KLCI) during the period of currency crisis. Order of integration was checked using Augmented Dickey Fuller and Phillip-Perons tests for unit root. The Johansen approach was used to test cointegration in multivariate system involved long run and short run estimations. The empirical evidence obtained from this study shows there exist a significant long run and short run relationship between the exchange rates variability and stock price behavior of the KLCI. Based on the asymmetric effects of the exchange rates and KLCI, we posit that the Malaysian Ringgit vis-a-vis Deutschmark and US Dollar had more exposure on the Fnancial Theory of Arbitrage i.e. the depreciation of the Ringgit will lead to the downfall of the KLCI. Nevertheless, the study found contrary evidence of the Malaysian Ringgit vis-a- vis Japanese Yen, Great Britain Pound and Singapore Dollar which follows the Macroeconomic Theory of Trade Channel i.e. the depreciation of the Ringgit will increase the performance of the KLCI. Finally, the overall findings suggest the fragility of the existing flexible exchange rate regime and the risk associated with such environment. Therefore, this research supports the call by the Prime Minister for a “New Global Financial Architecture”.